Harnessing Moringa oleifera through innovation: a pathway to economic growth - Mohd Tahir, Muhammad Shamsul Alan Niezam; Abu Samah, Siti Nurul Atikah; Yusuf, Nor Azma (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Moringa oleifera Lam., commonly known as the drumstick tree, ben oil tree, or miracle tree, is a fast-growing and drought-resistant member of the Moringaceae family widely cultivated in India, the Philippines, tropical Asia, Latin America, the Caribbean, and the Pacific Islands. This tropical perennial tree, which can reach 10–12 meters in height, has long been valued for its medicinal and culinary uses. It grows well in tropical and subtropical climates with annual rainfall ranging from about 250 to 2000 mm depending on soil conditions. The tree has silvery-grey rough bark, fragile spreading stems, branching older roots, and tripinnately compound leaves that are dark green on the upper surface and lighter green underneath.